178k views
1 vote
6 - 6x = 6x -10x + 4

User Kamrul
by
5.0k points

2 Answers

6 votes

Answer:

X=1

Am I right

Explanation:

6 - 6x = 6x - 10x +4

6- 6x = - 4x +4

6x +4x=4 +6

10x =10

Divide by 10

X=1

User Victorvartan
by
6.2k points
4 votes

Answer:

x=1

Explanation:

6 - 6x = 6x -10x + 4

Combine like terms

6 - 6x = -4x + 4

Add 6x to each side

6 -6x+6x = -4x+4+6x

6 = 2x+4

Subtract 4 from each side

6-4 = 2x+4-4

2 =2x

Divide by 2

2/2 = 2x/2

1 =x

User Basti
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.